In vitro assessment of protease production and stress tolerance of mutant isolates of Trichoderma sp. - Kucuk, Cigdem; Gezer, Tulay (Journal of Agriculture and Applied Biology, 2020)
Soil-borne plant pathogenic fungi cause serious losses in agricultural products. The antagonistic fungi for the control of plant diseases have increased efficiency and use of space has emerged as an alternative to other methods for the protection of agricultural products. One of the fungi used for this purpose is Trichoderma species. In this study mu-tant isolates of Trichoderma spp. were used. The resistance and pro-tease enzyme activities of mutant isolates against abiotic factors such as temperature, drought and salinity were investigated. Mutant iso-lates of Trichoderma sp. were showed differed in tolerance to differ-ent abiotic stress factors. Protease enzyme activity produced by iso-lates was influenced by the tested abiotic factors. In the medium con-taining 30% PEG, the highest protease activity was determined in Tm13 isolate. Indigenous Trichoderma strains produced proteases in high temperature, drought and saline conditions. This indicates that isolates may be promising candidates in agricultural production.